Rapid detection of pork in food products by electronic nose for halal authentication - Mokhtar, Nurjuliana; Che Man, Yaakob; Mat Hashim, Dzulkifly; Mohamed, A. K. S. (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
In this study, electronic nose (zNoseTM) was introduced as a new potential real time and fast technique to analyze the aroma of raw meat and processed meat for halal authentication. The zNoseTM was successfully tested for its ability to provide individual fingerprints of the aroma of pork and different types of sausages (beef sausage, chicken sausage and pork sausage). This is achieved using a visual odor pattern called VaporPrintTM, derived from the frequency of the surface acoustic wave (SAW) detector. Principal component analysis (PCA) was used to structure the data matrix. The different meat samples were separated along the first PC. The first PC described 94% of the total variance and showed four well defined groups: chicken sausage, pork sausage, beef sausage and pork. This percentage seemed sufficient to define a good model, especially for qualitative purpose. The high negative score of pork was determined by the highest amount of C8, C13 and C16 among all samples.